Problemas metodológicos en el estudio del mundo rural andalusí - Luis Gethsemaní Pérez Aguilar (Medievalista)
This paper collects some reflections about the theoretical and methodological framework related to the study of medieval rural settlements of Al-Andalus. We are intended to put a special stress on the bad habit, among many archaeologists, to put qualifier labels on population entities without a previous base rich, descriptive and systematic of the located sites to its further documentation. It deals primarily the problem concerning to the documentation of farmsteads (al-qurà). This term, that of farmstead (al-qarya), from the Arabic language, is originally a polysemous word that presents certain difficulties in interpreting the archaeological record. As an alternative we aim to propose a descriptive and flexible classification in order to realise a tipology of the andalusí sites.